Factors contributing to the surgical retreatment of mandibular fractures - João Gualberto de Cerqueira Luz; Rogerio Bonfante Moraes; Ricardo Pimenta D'Ávila; Marcos Kazuo Yamamoto (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The purpose of this retrospective study was to evaluate contributing factors in patients requiring surgical retreatment of mandibular fractures. Of all the patients with mandibular fractures who were treated using internal fixation at a trauma hospital over a seven-year period, 20 patients (4.7%) required a second surgery and thus composed the “reoperated” group. The control group comprised 42 consecutive patients with mandibular fractures who were treated at the same clinic and who healed without complications. Medical charts were reviewed for gender, age, substance abuse history, dental condition, etiology, location of fracture, degree of fragmentation, fracture exposure, teeth in the fracture line, associated facial fractures, polytrauma, time elapsed between trauma and initial treatment, surgical approach and fixation system. Statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) version 20.0; descriptive statistics and the chi-squared test were used to determine differences between groups. Significant differences in substance abuse (p = 0.006), dental condition (p < 0.001), location of fracture (p = 0.010), degree of fragmentation (p = 0.003) and fracture exposure (p < 0.001) were found. With regard to age and time elapsed between trauma and initial treatment, older patients (31.4 years, SD = 11.1) and a delay in fracture repair (19.1 days, SD = 18.7) were more likely to be associated with reoperation. It was concluded that substance abuse, age, dental condition, location of fracture, degree of fragmentation, fracture exposure and the time between trauma and initial treatment should be considered contributing factors to the occurrence of complications that require surgical retreatment of mandibular fractures.